Pengaruh Penerapan Rekam Medis Elektronik terhadap Kualitas Pelayanan pada Unit Gawat Darurat di Rumah Sakit Santosa Bandung Kopo - Rizki Tomi Resna Suhendar; Farida Yuliaty; Rukhiyat Syahidin; Taufan Nugroho; Vip Paramata; Kosasih Kosasih (Lembaga Pengembangan Kinerja Dosen, 2026)
This regulation, which requires all healthcare facilities to implement EMR by December 31, 2023, stemmed from the emergence of Health Ministerial Regulation No. 24 of 2022. Santosa Hospital, Bandung Kopo, has implemented EMR, but no research has been conducted on it. This study aimed to determine the effect of EMR implementation on service quality in the emergency unit at Santosa Hospital, Bandung Kopo. The research methods used were descriptive verification analysis and multiple linear regression analysis. Data collection used a questionnaire distributed to all emergency unit staff. The results of the descriptive analysis were generally considered very good. The results of the verification analysis, both partially, showed a negative and insignificant effect on system quality and service quality, while information quality and use statistics showed a positive and significant effect. Simultaneously, these positive and significant effects were proven, and the researchers recommend maintaining and further improving them.